Factors Associated With Home Births in Benin and Mali: Evidence From the Recent Demographic and Health Surveys - Bado, Aristide Romaric; Badolo, Hermann; Johnson, Ermel; Komboigo, Evelyne Bewendin; Padonou, Sètondji Géraud R.; Diawara, Fatou (Frontiers in Reproductive Health, 2022)
Introduction Identifying and understanding the factors associated with homebirths can contribute to improving maternal and child health and achieving the Sustainable Development Goals (SDGs). This study aimed to perform a comparative analysis of the factors associated with homebirths in Benin and Mali. Method This study is based on the most recent data from the Demographic Health Surveys conducted in Mali and Benin in 2018. The dependent variable was homebirth, and the explanatory variables were the individual characteristics of the woman, the distance to the health center, the place of residence, the number of prenatal consultations had, the frequency of media exposure, and the use of the Internet. The primary survey unit (PSU) was considered in the analysis to measure the effect of context on the choice of the place of delivery. Further, descriptive statistics and multilevel logistic regression analysis were used in the study. Results Educational level was associated with homebirth in Benin and Mali; Women with either no education or primary education are more likely to give birth at home. Women who didn't live close to a health facility were more likely to give birth at home than those who didn't face this problem in both countries. Not making visits for antenatal care (ANC) increases the odds of having a homebirth by 31.3 times (CI = 24.10–40.70) in Benin and 12.91 times (CI = 10.21–16.33) in Mali. Similarly, women who went on 1–2 ANC visits were more likely to give birth at home compared with women who made five or more ANC visits in both countries. The number of children per woman was also a significant factor in both countries. Women who often or regularly paid attention to the media messages were less likely to give birth at home compared with those who did not follow relevant media inputs (aOR = 0.42 [CI = 0.26–0.67] in Benin and aOR = 0.65 [CI = 0.50–0.85] in Mali). Conclusion Increasing the demand and uptake of women's health services by improving the availability and quality of services and establishing community health centers could help reduce the incidence of homebirths that can be risky and, thus, combat maternal and infant mortality.